2016
DOI: 10.1093/poq/nfw033
|View full text |Cite
|
Sign up to set email alerts
|

Research in and Prospects for the Measurement of Health Using Self-Rated Health

Abstract: Self-rated health (SRH)-for example, "in general would you say your health is excellent, very good, good, fair, or poor?"-is the most widely used measure of health across a range of survey research studies. This paper synthesizes extant research and provides a framework for future research on the measurement of health using SRH, focusing on four interrelated topics: the factors that influence respondents' health ratings, the survey measurement features of SRH, how SRH answers are analyzed, and the stated purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 90 publications
1
53
0
1
Order By: Relevance
“…Previous meta-analysis and review studies demonstrate a strong association between self-rated health and mortality (Ahmad et al 2014; Garbarski 2016; Idler and Benjamini 1997). Self-rated health has been found to be a reliable measurement of general health since respondents rated the same general health assessment within a period during which their health was unlikely to change.…”
Section: Methodsmentioning
confidence: 98%
“…Previous meta-analysis and review studies demonstrate a strong association between self-rated health and mortality (Ahmad et al 2014; Garbarski 2016; Idler and Benjamini 1997). Self-rated health has been found to be a reliable measurement of general health since respondents rated the same general health assessment within a period during which their health was unlikely to change.…”
Section: Methodsmentioning
confidence: 98%
“…Self-rated health (SRH) is one of the most widely used subjective measures of health status among older adults [3,4]. It was found to independently predict mortality, even after controlling for objective health measures [5].…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity analysis using the five-point self-rated health scale is reported in Table S4 in the Supplementary materials. Respondents have been found to take into account a wide range of health factors, including both aspects of physical as well as mental health, in forming an assessment of their own health (see Garbarski, 2016 for a research synthesis). Moreover, it has been shown that self-rated health is a valid and reliable measure of overall health and is predictive of mortality even after adjusting for specific health measures and other covariates (e.g.…”
Section: Methodsmentioning
confidence: 99%